Conjugated Linoleic Acid Grafting Improved Hemocompatibility of the Polycaprolactone Electrospun Membrane. (16th June 2020) - Tran, Nam Minh-phuong; Huynh, Toan Le-duc; Phan, Binh Ngoc; Dang, Nhi Ngoc-thao; Phan, Thang Bach; Ha, Huong Thi-thanh; Truong, Long Phuoc; Huynh, Phu Dai; Tran, Ngoc Quyen; Vo, Van Toi; Ha, Phuong Thu; Nguyen, Thi-Hiep
Abstract : Polycaprolactone (PCL) is a versatile biomaterial with a wide range of medical applications, but its use in blood-contacting devices is hampered due to insufficient hemocompatibility. In this work, electrospun polycaprolactone (PCL) membranes were chemically grafted with conjugated linoleic acid (CLA) to prevent induced blood coagulation. The density of grafted CLA and its effects on the morphology and wettability of the membranes were examined. The study also investigated how the membrane interacted with human whole blood and platelets to determine its antithrombotic properties. As the results suggested, the grafting caused a negligible effect on the physical properties of the membrane but greatly improved its compatibility with blood, showing that the approach can be investigated further for blood-contacting applications.